2009
DOI: 10.1007/s10763-009-9173-z
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Elementary Beginning Mathematics Teachers’ Efficacy Development

Abstract: The main purpose of this research was to explore the developmental process of and possible changes in beginning elementary mathematics teachers' efficacy. Beginning teachers with and without mathematics and science backgrounds were also compared to explore differences in their efficacy development. A multiple-case study method with a process and recursive design was employed in this study. The participants were six beginning elementary mathematics teachers purposefully selected from Taichung, Taiwan. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In classroom practices, the ability of teachers to produce desired results is called teacher efficacy or teacher selfefficacy beliefs. Teacher self-efficacy belief, a personal characteristic, has gained much attention in recent years (Chang, 2010;Bandura, 1997). Numerous studies in recent years have focused on the importance of the selfefficacy concept in understanding the behaviour of teachers and students in the learning process (Arigbabu, Abayomi, & Oludipe, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In classroom practices, the ability of teachers to produce desired results is called teacher efficacy or teacher selfefficacy beliefs. Teacher self-efficacy belief, a personal characteristic, has gained much attention in recent years (Chang, 2010;Bandura, 1997). Numerous studies in recent years have focused on the importance of the selfefficacy concept in understanding the behaviour of teachers and students in the learning process (Arigbabu, Abayomi, & Oludipe, 2009).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Teachers with high self-efficacy are more likely to develop challenging activities, help students succeed and persevere with students who have trouble learning (Kurz & Knight 2003). Studies on self-efficacy or the sense of efficacy of teachers have explored many fields of study and contexts, such as individual relationships, collective efficacy and goal (Kurz & Knight 2003), collective efficacy at the classroom level (Putney & Broughton, 2011), self-efficacy beliefs of novice and experienced teachers (Tschannen-Moran & Woolfolk Hoy, 2007;Marshall, Horton, Igo, & Switzer, 2007), self-efficacy of mathematics teachers (Marshall et al, 2007;Chang, 2010), self-efficacy of pre-service teachers (Cerit, 2010), self-efficacy of science teachers (Cantrell, Young, & Moore, 2017;Smolleck, Carla & Yoder, 2006;Arigbabu et al, 2009), self-efficacy and burn out in teaching (Friedman, 2003), teacher self-efficacy on the curriculum reform (McCormick & Ayres, 2009;Charalambous & Philippou, 2010) and self-efficacy on the technological pedagogical content (Lee & Tsai, 2008). No related study was found in the search of the literature based on the self-efficacy of teachers in the context of Sri Lanka.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Bandura's sources of TEBs have been studied through different approaches, with respect to their infl uence on teachers' effi cacy, and in connection to other educational parameters, such as the role of TEBs as coping resources against job stressors (Betoret 2009 ;Brand and Wilkins 2007 ;Chang 2009 ). Much of the relevant research (Charalambous et al 2008 ; Tschannen-Moran and Woolfolk Hoy 2007 ) has focused on the weight of each source in the formation of TEBs and also on their effect on TEBs of teachers being at different career stages.…”
Section: Sources Of Effi Cacy Beliefsmentioning
confidence: 99%
“…Bandura's sources have been examined both quantitatively (Chang 2009 ) and qualitatively (Usher and Pajares 2009 ), and efforts to build a stronger measure of the sources of self-effi cacy have been reported (Klassen et al 2011 ). Some social and contextual sources of TEBs, including the school climate and characteristics of the group of students, have also been examined (Tschannen-Moran and Woolfolk Hoy 2007 ).…”
Section: The Formation and Development Of Teacher Effi Cacymentioning
confidence: 99%